Inhibition of NOX2 reduces locomotor impairment, inflammation, and oxidative stress after spinal cord injury - Khayrullina, Guzal (J Neuroinflammation, 2015)
BACKGROUND: Spinal cord injury (SCI) results in the activation of the NADPH oxidase (NOX) enzyme, inducing production of reactive oxygen species (ROS). We hypothesized that the NOX2 isoform plays an integral role in post-SCI inflammation and functional deficits. METHODS: Moderate spinal cord contusion injury was performed in adult male mice, and flow cytometry, western blot, and immunohistochemistry were used to assess NOX2 activity and expression, inflammation, and M1/M2 microglia/macrophage polarization from 1 to 28 days after injury. The NOX2-specific inhibitor, gp91ds-tat, was injected into the intrathecal space immediately after impact. The Basso Mouse Scale (BMS) was used to assess locomotor function at 24 h post-injury and weekly thereafter. RESULTS: Our findings show that gp91ds-tat treatment significantly improved functional recovery through 28 days post-injury and reduced inflammatory cell concentrations in the injured spinal cord at 24 h and 7 days post-injury. In addition, a number of oxidative stress markers were reduced in expression at 24 h after gp91ds-tat treatment, which was accompanied by a reduction in M1 polarization marker expression. CONCLUSION: Based on our findings, we now conclude that inhibition of NOX2 significantly improves outcome after SCI, most likely via acute reductions in oxidative stress and inflammation. NOX2 inhibition may therefore have true potential as a therapy after SCI.